2006
DOI: 10.1074/jbc.m505024200
|View full text |Cite
|
Sign up to set email alerts
|

Transfer and Tunneling of Ca2+ from Sarcoplasmic Reticulum to Mitochondria in Skeletal Muscle

Abstract: The role of mitochondrial Ca 2؉ transport in regulating intracellular Ca 2؉ signaling and mitochondrial enzymes involved in energy metabolism is widely recognized in many tissues. However, the ability of skeletal muscle mitochondria to sequester Ca 2؉ released from the sarcoplasmic reticulum (SR) during the muscle contractionrelaxation cycle is still disputed. To assess the functional cross-talk of Ca 2؉ between SR and mitochondria, we examined the mutual relationship connecting cytosolic and mitochondrial Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 29 publications
(19 reference statements)
4
68
1
2
Order By: Relevance
“…Although Ca 2ϩ uptake by individual mitochondria is limited, aggregate Ca 2ϩ uptake by a sufficiently large number of strategically located mitochondria significantly blunts local and global cytoplasm Ca 2ϩ transients under physiological conditions (Rudolf et al, 2004). Similar results were found in single extensor digitorum longus (EDL) and soleus fibers (Shkryl and Shirokova, 2006). Moreover, contractile relaxation is accelerated in mitochondrial-rich skeletal muscle fibers, but not in more glycolytic fibers with fewer active and respiring mitochondria (Gillis, 1997).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Although Ca 2ϩ uptake by individual mitochondria is limited, aggregate Ca 2ϩ uptake by a sufficiently large number of strategically located mitochondria significantly blunts local and global cytoplasm Ca 2ϩ transients under physiological conditions (Rudolf et al, 2004). Similar results were found in single extensor digitorum longus (EDL) and soleus fibers (Shkryl and Shirokova, 2006). Moreover, contractile relaxation is accelerated in mitochondrial-rich skeletal muscle fibers, but not in more glycolytic fibers with fewer active and respiring mitochondria (Gillis, 1997).…”
Section: Introductionsupporting
confidence: 63%
“…As mitochondrial Ca 2ϩ uptake during transient elevations in cytoplasmic Ca 2ϩ requires communication through spatially confined, local signaling microdomains, the intimate mitochondrion-CRU assembly described here provides the structural framework required for local mitochondrial Ca 2ϩ uptake observed during SR Ca 2ϩ release in adult skeletal muscle (Gillis, 1997;Rizzuto et al, 1998;Shkryl and Shirokova, 2006). We found that tethers bridge SR to mitochondria on the side opposite to the location of RyRfeet.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have recently demonstrated that the local Ca 2ϩ coupling is regulated by the spacing between the ER and outer mitochondrial membrane and that the ER-mitochondrial interface is secured by protein tethers (8). Local [Ca 2ϩ ] regulation has also been shown to support the Ca 2ϩ signal propagation from the ryanodine receptors (RyR, the phylogenetic ancestors of the inositol 1,4,5-trisphosphate receptor) to the mitochondria in cardiac muscle cells (9,10) and in skeletal muscle (11)(12)(13). However, whether the local Ca 2ϩ communication between the SR and mitochondria is supported by physical coupling is yet to be elucidated.…”
Section: Activation Of Camentioning
confidence: 99%
“…1C (numbers of cells and events averaged are given in the Table 1). Fig 1D is [Ca 2ϩ ] increases in mitochondria upon Ca 2ϩ release (12) and mag-indo-1 loads in mitochondria as well as SR (11). When imaging in cells exposed to four inhibitors of mitochondrial Ca 2ϩ uptake ( Fig.…”
Section: Simultaneousmentioning
confidence: 99%